Sandmeyer-Type Reaction to Pinacol Arylboronates in Water Phase: A Green Borylation Process - Zhang, Jie; Wang, Xiaolong; Yu, Haitao; Ye, Jiahai (Synlett, 2012)
Copper(I)-catalyzed cross-coupling reactions of aryl diazonium salts with bis(pinacolato)diboron can proceed smoothly in the water phase at room temperature to give the corresponding arylboronate esters in good to high yields. The Sandmeyer-type borylation not only provides direct access to arylboronates bearing halo and acidic substituents, but also achieves a green borylation process.
Keywords: aryldiazonium salts; pinacol arylboronate; borylation; Sandmeyer reaction; 4-carboxylphenylboronate ester